1995
DOI: 10.1055/s-2007-973035
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone, Growth Hormone and IGF-I Responses to Acute and Chronic Resistive Exercise in Men Aged 55-70 Years

Abstract: We investigated the responses of serum testosterone (T) and human growth hormone (hGH) concentrations to a bout of heavy resistive exercise and the responses of T, hGH, and insulin-like growth factor I (IGF-I) to a 16 wk progressive resistive training program in 13 men (60 +/- 4 yrs). Body composition via hydrostatic weighing and muscle strength using a 3 repetition maximum (3RM) test on 6 variable resistance exercise machines were assessed before and after the training program. Fasting blood samples were draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
2
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 11 publications
9
59
2
3
Order By: Relevance
“…Exercise training has been shown to induce either signi®-cant changes 32 or no modi®cation 11,33 in gonadal and adrenal androgen levels in nondiabetic and diabetic men. Our results show an increase in DHEA levels induced by training, and an inverse relationship between changes in DHEA levels and changes in triglyceride and the sum of LDL and VLDL levels.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training has been shown to induce either signi®-cant changes 32 or no modi®cation 11,33 in gonadal and adrenal androgen levels in nondiabetic and diabetic men. Our results show an increase in DHEA levels induced by training, and an inverse relationship between changes in DHEA levels and changes in triglyceride and the sum of LDL and VLDL levels.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise studies comparing single-and multiple-set protocols differ not only with respect to training volume but also with respect to the equipment used for the measurements (9,25,31,41), exercise intensity (6,30,31,34), exercise mode (i.e., velocity [30,39,41]), periodization strategy (28,30,41), work until failure or not (22), and muscle groups (32,38). Also, the training experiences of the subjects investigated in these studies were very heterogeneous, ranging from untrained subjects to top-division footballers (25).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of acute exercise on testosterone stimulation have produced mixed results over the past few decades [67][68][69][70]. For example, a study investigating acute hormonal responses in elite junior Weightlifters found that the exercise protocol utilized caused a significant increase in serum testosterone, cortisol, GH, and whole blood lactate as compared to pre-exercise measures [68].…”
Section: Methods Of Increasing Testosterone Acute Exercisementioning
confidence: 99%
“…A recent study found that testosterone levels increased in both young (n=10) and middle-aged (n=8) men in response to acute, moderate intensity resistance exercise [67]. The results of another study indicated that serum testosterone levels were unchanged in men aged 55-70 years after a single bout of acute resistance exercise, despite an 18-fold increase in GH [70]. Linnamo et al, investigated the effects of maximal heavy resistance exercise on testosterone and GH levels in both men and women and found that GH increased in both genders while testosterone levels increased only in men following exercise [69].…”
mentioning
confidence: 98%